2019
DOI: 10.17219/dmp/100444
|View full text |Cite
|
Sign up to set email alerts
|

Effect of acute methyl methacrylate vapor inhalation on smokers’ and non-smokers’ respiratory function in a sample of male dentistry students

Abstract: Background. Methyl methacrylate (MMA) is one of the widely used organic monomers in dentistry. It may cause multiple adverse reactions, ranging from allergic reaction to systemic toxicity. Dentistry students are exposed to MMA in an acute manner; however, the concentration of its vapor cannot be estimated well. Objectives. The aim of this study was to evaluate the effect of acute MMA vapor inhalation on the pulmonary function of dental students, both smokers and non-smokers. Material and methods. Thirty-eight … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…However, serious problems have not been reported for the inhalation of polymethyl methacrylate (PMMA) ingredients, although MMA may irritate the eyes, skin, and respiratory system [ 9 ]. Dental students, both smokers and non-smokers, exposed to acute MMA vapor inhalation demonstrated a moderate restriction of pulmonary function [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, serious problems have not been reported for the inhalation of polymethyl methacrylate (PMMA) ingredients, although MMA may irritate the eyes, skin, and respiratory system [ 9 ]. Dental students, both smokers and non-smokers, exposed to acute MMA vapor inhalation demonstrated a moderate restriction of pulmonary function [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…A large body of evidence has been accumulated regarding the release of residual monomers and toxicity of acrylic resin in dentistry, with clinical observations and in vitro experiments being predominant [ [4] , [5] , [11] , [12] , [13] , [14] ].However, in vivo studies are comparatively sparse [ 10 , 15 ]. Studies in animals have demonstrated the neurotoxic potential of formaldehyde and that exposure to this compound may cause deficits in spatial learning and memory [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, serious problems hasn't been reported by inhaling poly methyl methacrylate (PMMA) ingredients, although MMA may irritate eyes, skin and respiratory system [9]. Acute inhalation of MMA vapor induced a moderate restriction of pulmonary function in dental students, both smokers and non-smokers [10].…”
Section: Introductionmentioning
confidence: 99%
“…There is plenty of evidence concerning about residual monomers release and toxicity of acrylic resin used in dentistry [9], especially with clinical observations and in vitro experiments [4,5,[11][12][13][14], but few in vivo studies [10,15]. Clinical observations are highly subject to bias, such as non-commitment of the individual to the treatment or exposure of these individuals to external factors that may interfere with the research, and in vitro experiments do not have system integrity to assess the real impact of a substance in a complete organism, so animal models are better suited for these types of studies since they present di cult to simulate responses in cell culture [16].…”
Section: Introductionmentioning
confidence: 99%